Spillover Effects of the Minimum Wage Introduction Based on Horizontal Fairness: A Lab Experiment - Demirtas, Burak Kagan (John Wiley & Sons Ltd, 2022)
This paper analyses how a minimum wage introduction affects reservation wages and wage offers based on horizontal fairness with a lab experiment with two experimental settings. The first experimental setting was applied to two types of workers (low or high skills), whereas there are one type of workers in the second setting but two types of sectors, covered and uncovered sectors, depending on whether the minimum wage is enforced. Results show the minimum wage introduction generates spillover effects on the high-skilled workers' reservation wages and wage offers, whereas there is no evidence of the spillover effect on the uncovered sector.
Demirtas, Burak Kagan/0000-0001-9477-8128;